Conflicts in the Movie “Avengers: Infinity War” Directed By Anthony and Joe Russo - M. Rabiddin Hussien (Universitas Terbuka, 2024)
The objective of this study was to describe the conflicts and the cause the conflicts that happen in the movie: “Avengers: Infinity War”. This study was conducted using qualitative descriptive research design. The data of this study were the utterances or expressions, facial expressions, body gestures, contexts and scenes in the movie “Avengers: Infinity War” which indicated conflicts. The data were collected using documentation review. The data was analized using types of conflicts theory by Kenney in Viyana (2014) and cause of conflicts by Folarin (2014). The findings of this research are there are 22 conflicts in the movie “Avengers: Infinity War” which consist of 9 (nine) external conflicts and 13 (thirteen) internal conflicts. Man vs Man conflicts as external conflicts result mostly in physical activities. Meanwhile, Man vs Self conflicts as internal conflicts happen to 9 (nine) different characters (Loki, Thor, Bruce “Hulk”, Tony Stark “Iron Man”, Quill, Gamora, Dr. Strange, Wanda, and Thanos). Mostly, internal conflict happens in dilemma and anger. In addition, in the cause of conflict, there are psychological theory of conflict and realist theory of conflict. Psychological theory of conflict mostly happens in internal conflicts, meanwhile realist theory of conflict mostly happens in external conflicts.